Risk factors for sporadic hepatitis E infection: a systematic review and meta-analysis - Pavio, Nicole (2021)
Hepatitis E virus (HEV) is one of the main causes of viral hepatitis infection worldwide. Sources of contamination can vary greatly according to geographical regions and HEV genotypes. HEV is endemic and responsible for large waterborne epidemics involving human HEV-1 or HEV-2 genotypes in regions with limited sanitation, in contrast to industrialized countries, where HEV is mainly a foodborne zoonosis involving HEV-3 and HEV-4 zoonotic genotypes. Limited data on HEV source attribution are available, and all possible sources and transmission pathways of HEV are not fully identified. A systematic review and a meta-analysis of case-control and cohort studies (including transversal studies) were performed to determine the main risk factors associated with sporadic hepatitis E infection. Suitable scientific articles were identified through a systematic literature search and subjected to a methodological quality assessment. From each study, odds-ratio (OR) measures were extracted/calculated, as well as study characteristics such as population type, design, and risk factor hierarchy. Mixed-effects meta-analyses models were adjusted by population type to appropriate data partitions. Seventy-seven cohort and case-control studies conducted between 1986 and 2016 and investigating risk factors in mixed population, susceptible population, and pregnant women, were included in this meta-analysis. Hepatitis E cases were defined with serological exams and differentiated whenever the serological exam is associated or not with symptoms. This meta-analysis identified the parenteral pathway (blood transfusion, tattooing or IV injection, dialysis or hemodialysis), and routes of infection related to contaminated water, animal contact (occupational exposure) and consumption of foods as relevant risk factors for hepatitis E infection. With regards to the role of food, as suspected and sometimes proven in several studies, pig meat, pork sausages, and game meat are identified as significant risk factors for HEV, in particular undercooked pig meat, or meat preparations containing pig liver. In addition, consumption of shellfish (oysters and mussels), in which HEV can accumulate when water is environmentally contaminated (from animal or human origin), is also associated with the detection of anti-HEV antibodies. The results of this meta-analysis show that symptomatic and infected cases share the most explainable risk factors, and are in agreement with recent studies conducted in Europe. This meta-analysis reveals that some sources such as consumption of insufficiently treated water, shellfish, or vegetables are under-investigated. Future case-control studies should include population at risk but under-investigated, such as transplant recipients, pregnant women and children, and investigate other potential sources of HEV.